Microsoft Excel 2010 level 1 - Rutkosky, Nita (Paradigm, 2011)
Benchmark Series: Microsoft Word Level 1 builds students' introductory skills in Word 2010, and helps develop critical thinking and decision-making skills. Case study assessments at chapter and unit levels test students' abilities to solve problems independently Project-based approach creates a realistic context for learning practical skills